18. FACTORS AFFECTING THE SELECTION OF LAPAROSCOPIC SURGERY FOR THE TREATMENT OF OVARIAN TUMORS IN PREGNANT WOMEN AT HA NOI OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To assess some factors related to the choice of treatment for ovarian tumors in pregnant women through laparoscopic surgery at Hanoi Obstetrics and Gynecology Hospital from 2019 to 2023.Material and methods: A cross-sectional descriptive study using retrospective sampling was conducted on 74 pregnant women with ovarian tumors who were treated with laparoscopic surgery during pregnancy at Hanoi Obstetrics and Gynecology Hospital from January 1, 2019, to December 31, 2023.Results: The most common age group of pregnant women with ovarian tumors who underwent laparoscopic surgery during pregnancy is between 20 and 35 years old (94.5%), with 74.3% of cases having ≤ 1 child. Most patients were admitted due to lower abdominal pain, and 74.3% underwent emergency surgery. The characteristics of patients requiring emergency surgery include: 90% were at a gestational age of ≤ 12 weeks, 100% had torsion or rupture of the tumor, and 82.8% had O-RADS ≥ 3 (p < 0.05). The laparoscopic cystectomy mainly included: absence of abdominal pain (94.7%), non-torsioned tumors (100%), and O-RADS 1-2 (82.2%) with p < 0.05.Conclusions: The indication for emergency laparoscopic surgery for the treatment of ovarian tumors in pregnant women is established for tumors with complications (torsion, rupture), even when the gestational age is ≤ 12 weeks and the O-RADS index is ≥ 3 (p < 0.05). Laparoscopic cystectomy can help preserve the ovaries and can be applied in cases of non-painful abdominal conditions and non-torsioned, non-ruptured ovarian tumors (p < 0.05).
Keywords: Surgical methods for ovarian tumors in pregnant women; indications for surgery for ovarian tumors in pregnant women; ovarian tumors in pregnant women